A walk from the wild edge - Tyler, Jake (Michael Joseph, 2021)
After coming terrifyingly close to suicide, Jake Tyler was determined to take back control of his life from the clutches of depression. With only his running gear and a backpack, he stepped out of his house in Brighton and began a 3000-mile journey around the UK. In documenting every step of his journey, Jake shares the ways in which his mission was enhanced by the kindness of strangers who took him in for the night, or let him talk when the darkness engulfed him. This is both the story of Jake's journey around the country and his journey to better understand himself, ultimately finding peace and acceptance with his mental health.